Rekayasa Material Dan Modifikasi Desain Pisau Pencacah Limbah Plastik Di Tpsa Bagendung - Winda Sri Jaman; Asadian Puja Enggita; Adi Widodo; Hendra Setyawan (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
Plastic waste is a serious environmental problem in Indonesia due to its non-biodegradable nature. One of the management efforts is carried out at TPSA Bagendung through the use of a plastic shredding machine. However, the shredder blades often experience wear and chipping, which reduces machine performance. This study aims to redesign the blade material and geometry to improve wear resistance and hardness. The initial material was medium carbon steel with an average hardness of 44.46 HRC and a composition of 0.410% C; 0.376% Cr; 1.14% Mn; and 0.223% Si. The replacement material was selected from D2 steel with higher carbon and chromium content, followed by heat treatment, resulting in an average hardness of 60.61 HRC with a composition of 1.62% C; 12.1% Cr; 0.270% Ni; 0.778% Mo; and 0.742% V. Metallographic analysis using an optical microscope at 1500× magnification after Nital etching revealed a dominant needle-shaped martensitic structure with chromium carbide precipitates uniformly distributed along grain boundaries. This microstructure strengthens the matrix, enhances wear resistance, and directly correlates with the increased hardness. In addition, the modification of the bolt slot length from 40 mm to 45 mm provided greater adjustability of the blade position, thereby extending its service life. Overall, the combination of material engineering and design modification resulted in shredder blades with improved mechanical properties, higher wear resistance, and longer durability compared to the original material.